Transplantationsosteoporose - Fahrleitner-Pammer, A.; Bergthaler, M.; Dimai, H. P. (Osteologie, 2018)
Die Transplantation hat sich während der letzten Jahrzehnte zu einer etablierten Therapie terminaler Organerkrankungen entwickelt. Die derzeit verfügbaren immunsuppressiven Therapieschemata, welche neben Steroiden auch Calcineurin Inhibitoren beinhalten, haben zu einem besseren Langzeitüberleben geführt. Spätkomplikationen wie die Transplantationsosteoporose gewinnen dadurch an Bedeutung. Der ausgeprägteste Knochenmasseverlust tritt während der ersten 6-12 Monate nach erfolgreicher Transplantation auf und ist charakterisiert durch eine hohe Frakturinzidenz, welche in Abhängigkeit vom transplantierten Organ bei über 50 % liegt. Diese frühe Phase ist geprägt durch eine Entkoppelung des Knochenstoffwechsels mit einer unterdrückten Knochenformation und gesteigerten Resorption. Bei Langzeitüberlebenden spielen andere Faktoren, wie eine eingeschränkte Nierenfunktion, ein Hypogonadismus und ein sekundärer Hyperparathyreodismus eine Rolle. Therapeutische Ansätze beinhalten eine Prävention schon zum Zeitpunkt der Evaluierung für eine Transplantation sowie unmittelbar im Anschluss an die Transplantation eine unabhängig von der Knochendichte frühestmögliche spezifische Therapie.Transplantation has derived as an established treatment option for patients with end stage organ failure. Currently available immunosuppressive treatment regimens including calcineurin inhibitors on top of steroids have led to an improved graft and patients´ survival. Therefore, not only the number of transplantations but also the number of patients has been constantly rising and late complications such as transplantation bone disease have become of growing importance. Candidates for organ transplantation are likely to have impaired bone health, and screening for osteoporosis should include spinal X-rays, bone densitometry and laboratory tests in order to treat patients already prior transplantation if necessary. Bone loss after transplantation is related to the well known side effects of immunosuppressants in combination with immobilization. After surgery, immediate osteoprotective therapy is crucial, independently of bone mineral density, as rapid bone loss with suppressed bone formation and increased bone resorption characterizes the first 6-12 months following surgery. This phenomenon triggered by high dose steroid therapy induces a so-called “uncoupling” of bone formation and bone resorption with a remarkably low bone formation rate accompanied by a high bone resorption leading to rapid bone loss with a high fracture rate up to more than 50%. The duration of osteoprotective therapy depends not only on the type of graft and the dosage and duration of steroid treatment but also on comorbidities like hypogonadism, secondary hyperparathyreodism and chronic kidney disease. On top of vitamin D repletion therapy, oral and intravenous bisphosphonate therapy are the most promising treatment options in order to stabilize and increase bone mineral density and reduce fracture risk in this special group of patients. Monitoring of bone health should become standard care in patients following organ transplantation.
Keywords: Organtransplantation; Fraktur; Osteoporose; immunsuppressive Therapie